What's love got to do with it? Understanding local cognitive and affective responses to wind power projects. (January 2021) - Russell, Aaron; Firestone, Jeremy
Highlights: A cognition and affect focused model is used to explore wind project neighbors' attitudes. Pre- and post-project construction neighbors are compared representing the whole U.S. Post-construction move-in correlates with more positive attitude. Affect(emotions) show to be more predictive of attitude in general. Cognitive evaluation has a larger effect on attitude post-construction. Abstract: Negative perceptions of renewable energy development can lead to protest, resulting in project delay or failure. Alternatively, good communication and sensitivity to community feelings are pathways to success. While literature referencing the social aspects of wind power siting have become widespread, analyses which include individuals' affect or emotional dimensions are rarer. Appreciation for emotional as well as cognitive perceptions is crucial for adequate understanding of not just consumptive or productive aspects of energy, but entire systems. We use a US national cross-sectional data set of 1705 individuals who live within 8 km of a wind turbine collected in a research project led by Lawrence Berkeley National Lab in a random probability-based phone, mail, and online survey in 2016. We hypothesize that individuals who moved-in prior to commencement of project construction will differ markedly from those who move in afterwards in terms of the cognitive and affective aspects of their attitude formation, and in particular, that negative emotions will be distinct. Variables include emotions such as pride, anger, and annoyance, perceptions of fit with the landscape, descriptions of the turbines as industrial and whether they added to or detracted from the community. We find affect is the stronger driver of attitude, but not merely by negative emotions. When we include both cognitive and affective variables, individual emotions are generally more predictive of attitude for pre-construction neighbors and cognitive variables such as wind being an effective means of climate mitigation and perception of property value change are stronger post-construction.